Changes in the Qualitative and Quantitative Composition of Essential Oils of Clary Sage and Roman Chamomile During Steam Distillation in Pilot Plant Scale - Wagner, Susanne; Pfleger, Angela; Mandl, Michael; Böchzelt, Herbert (IntechOpen, 2012)
None